Rigid internal fi xation of zygoma fractures: A comparison of two-point and three-point fi xation - Parashar Atul; K. Sharma Ramesh; Makkar Surinder (Indian Journal of Plastic Surgery)
Background:Displaced fractures of the zygomatic bone can result in significant functional and aesthetic sequelae. Therefore the treatment must achieve adequate and stable reduction at fracture sites so as to restore the complex multidimensional relationship of the zygoma to the surrounding craniofacial skeleton. Many experimental biophysical studies have compared stability of zygoma after one, two and three-point fixation with mini plates. We conducted a prospective clinical study comparing functional and aesthetic results of two-point and three-point fixation with mini plates in patients with fractures of zygoma.Materials and Methods:Twenty-two patients with isolated zygomatic fractures over a period of one year were randomly assigned into two-point and three-point fixation groups. Results of fixation were analyzed after completion of three months. This included clinical, radiological and photographic evaluation.Results:The three-point fixation group maintained better stability at fracture sites resulting in decreased incidence of dystopia and enophthalmos. This group also had better malar projection and malar height as measured radiologically, when compared with the two-point fixation group.Conclusion:We recommend three-point rigid fixation of fractured zygoma after accurate reduction so as to maintain adequate stabilization against masticatory forces during fracture healing phase.